PENGARUH MODEL PEMBELAJARAN MIND MAPPING BERBANTUAN MEDIA POWER POINT TERHADAP HASIL BELAJAR MATEMATIKA - Gozali , Imam; Marsidi; Panglipur, Indah Rahayu (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
Students' mathematical learning results are influenced by many variables, including students, parents, schools, curricula, and mathematics itself. Preliminary observations showed that 27.7% of students received a score above 75 and 72.3% received a rating below 75. The minimum score for the exam was 75, which is the average grade. Many factors can contribute to poor student learning outcomes, including the role of teachers as instructors and their influence on students in creating and using inappropriate learning strategies. An alternative that can be developed on a model with learning is to use a mind mapping defence model. This survey aims to find out how much influence it has found on the mind mapping defense model with the help of power points. The type of quantitative research used in this study is the design of a single group pretest-posttest. The test results are known to have a thitung value of 3.27. Thitung values are matched to with Table values with a significant upgrade of a=0,05 and obtained Table Values of 2.063. Thitung Values are derived that is greater than Table Value (thitung = 3.27 > ttable = 2.063 then Ha is accepted, that is, using the learning model of Mind Mapping and PowerPoint media, the student's learning results can be influenced.